Sex differences in emotional perception: Evidence from population of Tuvans (Southern Siberia) - Mezentseva, A. A.; Rostovtseva, V. V.; Ananyeva, K. I.; Demidov, A. A.; Butovskaya, M. L. (Frontiers in Psychology, 2022)
Prior studies have reported that women outperform men in nonverbal communication, including the recognition of emotions through static facial expressions. In this experimental study, we investigated sex differences in the estimation of states of happiness, anger, fear, and disgust through static photographs using a two-culture approach. This study was conducted among the Tuvans and Mongolian people from Southern Siberia. The respondents were presented with a set of photographs of men and women of European and Tuvan origin and were asked to interpret each of them. They were asked: “What does the person in the photo feel?” We found that the Tuvans easily identified happiness and anger; however, the level of accuracy of fear and disgust recognition was low. No sex differences in the recognition of happiness, disgust, and fear were observed. However, anger recognition was significantly moderated by the perceiver’s sex and the origin of the model. Compared to Tuvan men, Tuvan women were significantly less accurate in identifying anger in male Tuvans. Furthermore, the age effect was found in recognition of fear: older Tuvans were more accurate while recognizing the fearful faces of Tuvan, but not the European models.